2024
DOI: 10.1186/s12911-024-02480-9
|View full text |Cite
|
Sign up to set email alerts
|

Post-surgery survival and associated factors for cardiac patients in Ethiopia: applications of machine learning, semi-parametric and parametric modelling

Melaku Tadege,
Awoke Seyoum Tegegne,
Zelalem G. Dessie

Abstract: Introduction Living in poverty, especially in low-income countries, are more affected by cardiovascular disease. Unlike the developed countries, it remains a significant cause of preventable heart disease in the Sub-Saharan region, including Ethiopia. According to the Ethiopian Ministry of Health statement, around 40,000 cardiac patients have been waiting for surgery in Ethiopia since September 2020. There is insufficient information about long-term cardiac patients’ post-survival after cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…These factors undermine the accuracy of the waiting time results. The duration of waiting time to get surgery was found to be highly correlated with and served as the most significant predictor of mortality among cardiac patients after surgery [ 48 ]. However, there are some papers that have suggested that the outcome of the surgery is not influenced by the waiting time [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors undermine the accuracy of the waiting time results. The duration of waiting time to get surgery was found to be highly correlated with and served as the most significant predictor of mortality among cardiac patients after surgery [ 48 ]. However, there are some papers that have suggested that the outcome of the surgery is not influenced by the waiting time [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%